Investigating anode off-gas under spark-ignition combustion for SOFC-ICE hybrid systems. (May 2022) - Ran, Zhongnan; Longtin, Jon; Assanis, Dimitris
Solid oxide fuel cell – internal combustion engine (SOFC-ICE) hybrid systems are an attractive solution for electricity generation. The system can achieve up to 70% theoretical electric power conversion efficiency through energy cascading enabled by utilizing the anode off-gas from the SOFC as the fuel source for the ICE. Experimental investigations were conducted with a single cylinder Cooperative Fuel Research (CFR) engine by altering fuel-air equivalence ratio (ϕ), and compression ratio (CR) to study the engine load, combustion characteristics, and emissions levels of dry SOFC anode off-gas consisting of 33.9% H2, 15.6% CO, and 50.5% CO2 . The combustion efficiency of the anode off-gas was directly evaluated by measuring the engine-out CO emissions. The highest net-indicated fuel conversion efficiency of 31.3% occurred at ϕ  =  0.90 and CR = 13:1. These results demonstrate that the anode off-gas can be successfully oxidized using a spark ignition combustion mode. The fuel conversion efficiency of the anode tail gas is expected to further increase in a more modern engine architecture that can achieve increased burn rates in comparison to the CFR engine. NOx emissions from the combustion of anode off-gas were minimal as the cylinder peak temperatures never exceeded 1800 K. This experimental study ultimately demonstrates the viability of an ICE to operate using an anode off-gas, thus creating a complementary role for an ICE to be paired with a SOFC in a hybrid power generation plant.